2008
DOI: 10.1186/1743-422x-5-81
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new HIV-1 Gag-specific cytotoxic T lymphocyte responses in BALB/c mice

Abstract: Background: As HIV-specific cytotoxic T cells play a key role during acute and chronic HIV-1 infection in humans, the ability of potential anti-HIV vaccines to elicit strong, broad T cell responses is likely to be crucial. The HIV-1 Gag antigen is widely considered a relevant antigen for the development of an anti-HIV vaccine since it is one of the most conserved viral proteins and is also known to induce T cell responses. In the majority of studies reporting Gag-specific cellular immune responses induced by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Specifically, Balb/c mice were immunized with the HIV-1 Gag protein alone or in combination with Tat and, ten days after immunization, fresh splenocytes from immunized mice were assayed by IFNγ Elispot to evaluate T cell responses directed against previously identified Gag-derived peptides [31] containing eight CD8 epitopes (Table S1). As shown in Figure 1C, immunization with Gag alone did not induce detectable Gag-specific T cell responses, whereas immunization with the Gag protein in the presence of Tat elicited significant Gag-specific responses directed against all tested CD8 epitopes.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, Balb/c mice were immunized with the HIV-1 Gag protein alone or in combination with Tat and, ten days after immunization, fresh splenocytes from immunized mice were assayed by IFNγ Elispot to evaluate T cell responses directed against previously identified Gag-derived peptides [31] containing eight CD8 epitopes (Table S1). As shown in Figure 1C, immunization with Gag alone did not induce detectable Gag-specific T cell responses, whereas immunization with the Gag protein in the presence of Tat elicited significant Gag-specific responses directed against all tested CD8 epitopes.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, mice vaccinated with Env or with V2-deleted Env in combination with Tat responded to 17 peptides, 12 more than mice vaccinated with the Env proteins alone. The effect was specific as Tat did not affect Th2-type responses to these structural HIV proteins [97,214]. In contrast with these results, using a DNA vaccination approach Agwale and co-worker reported that vaccination with a bi-cistronic gp120-tat DNA diminished IFN-γ CD8+ T cell responses against the immunodominant HIV-1 gp120 Env peptide in mice compared to those induced by vaccination with DNA encoding gp120 alone and that the effect of Tat was abolished by a sequence deletion (aa 31-50) in the cys-core domain of Tat (2).…”
Section: Immunomodulatory Activity Of Hiv-1 Tatmentioning
confidence: 94%
“…These combined vaccines should be more efficacious because they may attack the virus on early and late gene products. In these studies, mice vaccinated subcutaneously with the HIV-1 Gag, Env, or V2-deleted Env protein antigens in combination with the biologically active Tat protein developed strong humoral and cellular (Th1-and Th2-type) immune responses against Tat and the co-administered antigen and broadened the Th1-type and CTL responses against Gag or Env antigens [97,214]. In addition, these strategies were safe, immunogenic, and effective in containing SHIV 89.6P replication in cynomolgus macaques [Ensoli et al, manuscript in preparation], and based on these preclinical results, a Tat/V2-deleted Env protein vaccine will soon undergo phase I clinical trial testing in Italy (http://www.hiv1tat-vaccines.info/).…”
Section: Tat In Combination With Hiv-1 Env And/or Gag Structural Antimentioning
confidence: 99%
“…CTLs play an important role in host defense against HIV-1 by recognizing and eliminating infected cells (Cellini et al, 2008; Kitano et al, 2008; Westrop et al, 2009; Bangham, 2009). Identification of CTL epitopes correlated to immune protection is important for the development of vaccines that enhance T cell-mediated immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most conserved viral proteins in HIV-1 and it is known to induce protective T-cell responses in animal models and in humans, making it a good candidate for development of an anti-HIV vaccine (Cellini et al, 2008; Kiepiela et al, 2004; Zuniga et al, 2006). Identification of CTL epitopes in this region is important and will help to understand host and virus interactions and contribute to vaccine development (Bangham, 2009).…”
Section: Introductionmentioning
confidence: 99%